RNA polymerase III initiation on coligo DNA templates containing loops of variable sequence, size and nucleotide chemistry - Patel, Joy; Hoffmann, Niklas A.; Müller, Christoph W. (Gene, 2017)
Circularized oligonucleotides, or coligos, were previously found to serve as RNA polymerase III (Pol III) templates in vitro and in human tissue culture cells. Here we randomized the 12-nucleotide larger loop (L-loop) of a well characterized coligo and found unexpectedly that in vitro transcription by FLAG-Pol III was not significantly affected. This observation allowed us to test the variable of coligo L-loop size separately from the variable of its sequence. Transcription efficiency increased with L-loop size from 3 to 12 nucleotides of randomized sequence, and the smallest loop forced initiation to move into the stem region. To test further the need for any specific sequence we compared seven nucleotide L-loops composed of random, abasic and abasic-acyclic nucleotides, and all supported transcription by Pol III. Transcription of a series of coligos containing twelve contiguous randomized nucleotides placed at different locations within the coligo structure provided further evidence that the stem-loop junction structure is important for precise initiation. Nearly the same transcript pattern was formed in vitro by Pol III from yeast and human cells. Overall, these experiments support structure, rather than L-loop sequence, as the major determinant of coligo transcription initiation by Pol III.